Integrating drainage, ecology and recreation in a campus river: a case study of International Islamic University - Mohd. Yaman, Maheran; Nik Abdul Rahman, Nik Ismail Azlan (IIUM, 2009)
ABSTRACT This paper describes the planning, design and contruction of multiuse drainage facilities of Sungai Anak Pusu which runs across the central campus if the International Islamic University of Malaysia in Gombak. The Master Drainage Plan provides for the best management practices (BMPs) that provide retention ponds, detention facilities for surface runoff, open space, recreational greenway corridors and riparian habitat. This campus is one of the first local institutionof higher learning to implement a comprehensive plan for quality enhancement of the drainage system for a campus river. Under the plan, all surface water is routed through specially designed extended detention basins prior discharge into the receiving river. Selected stabilization measures are used along the river to preserve their natural character, ecological aspects and to provide recreational facilities.